The implication of IFRS financial instruments disclosure on value relevance - Taleb Alsarayreh; Mohammad Saleh Altarawneh; Ahmed Eltweri (Journal of Risk and Financial Management, 2022)
The main objective of this research is to examine the effects of financial instruments declared under IFRSs on value relevance over thirteen years. The research sample included 35 European enterprises that were listed on the main market of the London Stock Exchange from 2007 to 2019. This study focuses on the adoption of IFRS.7 and IAS.32 disclosure standards, in line with previous studies. The Ohlson model (1995) was utilised in the study to evaluate the dependent variable since it is the module used most often in determining value relevance. The findings indicated that financial knowledge about financial instruments (FI) was typically valuable throughout the research. In addition, the significance of financial instruments and other disclosures when examining sub-components were not valued as relevant but rather provided information regarding the kind and level of exposure to FI risks. Furthermore, the earnings and book value of the common equity have a favourable impact on the value relevance. Hence, the key contributions of this study went beyond enriching the body of literature to make recommendations regarding the most influential determinant among financial instrument items that positively enhance value relevance.
Keywords: 650; financial instruments; London stock exchange; IASB; IFRS; Olson model; value relevance